Don Juan Wolfganga Amadeusa Mozarta w reżyserskiej interpretacji Lii Rotbaumówny – próba rekonstrukcji - Rudnicka, Justyna (Res Facta Nova, 2019)
Don Juan by Wolfgang Amadeus Mozart, directed by Lia Rotbaum (Opera Wrocławska, 1969), turned out to be an unorthodox staging supported by deep theoretical reflection. This article attempts to reconstruct this staging, on the basis of what is known as the work’s documentation (director’s copy, photographs, opera programme), reviews, accounts by the singers, as well as the director’s theoretical writings. Don Juan in the interpretation of Lia Rotbaum is an ambivalent figure, who combines contradictory attitudes. He is not a thoroughly negative protagonist; it is the other characters in the opera who, like mirrors, reflect other aspects of his activities. For this reason the director makes the question of responsibility of one person towards another the main theme of the work. Directorial techniques include the use of the revolving stage to give tempo and dynamics to individual scenes; removing and changing the sequence of some musical fragments; operating with studied, rich stage movement, and a highly ordered stage design.